INHERITANCE OF COAT COLOR OF KEJOBONG GOAT IN PURBALINGGA REGENCY, CENTRAL JAVA, INDONESIA - T. Permatasari; S. Sutopo; E. Kurnianto (Diponegoro University, 2014)
The objective of this research was to examine the inheritance of coat color pattern of Kejobonggoat. The material used was goat family with clear lineage, in which the number of samples were 130Kejobong family, consisted of 201 kids, 130 does and 51 bucks. Coat color of black, black white, blackbrown, brown, white brown and white, were observed. The coat color types were classified andgenetically grouped according to the pigmentation types and color patterns. Probability compilationgene of coat color of Kejobong goat were B-C-S-ii (black), – cc – – (white), BBC-ssii (black white),BbC-ssii (black brown), bbC-ssii (white brown) and bbC-S-ii (brown). Inheritance of coat colorobserved and fenotipe ratio expected were used to calculate Chi-square. Results of study showed that theinheritance of coat color pattern of Kejobong goat were not in Hardy-Weinberg equilibrium withexeption of mating between black and black brown and mating between brown black and white brownshowing similarity in observations and expectations.